2021
DOI: 10.1021/acsomega.0c05092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Co–ZnO and Evaluation of Its Photocatalytic Activity for Photodegradation of Methyl Orange

Abstract: Photocatalysis is one of the techniques used for the eradication of organic pollutants from wastewater. In this study, Co−ZnO was tested as a photocatalyst for the degradation of methyl orange under irradiation of visible light. Co−ZnO loaded with 5%, 10%, and 15% Co was prepared by the precipitation method. The advanced techniques including X-ray diffraction, X-ray photoelectron spectroscopy, diffuse reflectance UV−visible spectroscopy, photoelectrochemical measurements, temperatureprogrammed desorption, phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(101 citation statements)
references
References 73 publications
5
96
0
Order By: Relevance
“…Several conventional methods have been used to treat wastewater, including biological treatment, anaerobic, aerobic, and electrochemical methods, oxidation, reduction, flotation, flocculation, precipitation, and adsorption. However, these methods cannot completely degrade organic pollutants [1][2][3][4][5][6]. Photocatalysis based on illumination of semiconductor powder for removal of organic contaminants from water is environmentally friendly and cost effective, and it has; therefore, attracted particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Several conventional methods have been used to treat wastewater, including biological treatment, anaerobic, aerobic, and electrochemical methods, oxidation, reduction, flotation, flocculation, precipitation, and adsorption. However, these methods cannot completely degrade organic pollutants [1][2][3][4][5][6]. Photocatalysis based on illumination of semiconductor powder for removal of organic contaminants from water is environmentally friendly and cost effective, and it has; therefore, attracted particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…6. If Co and Zn dissolve in identical proportions, it can be assumed that Co is uniformly doped in the zincite phase (Adeel et al, 2021). The peak of zincite (2Ɵ:68) disappears, in the XRD pattern of MSFT by the baking process and this peak substitutes with cobalt sulphate in the XRD patterns of B-MSFT.…”
Section: Extraction Of Base Metalsmentioning
confidence: 99%
“…It was found that catalytic activity decreased with increase in initial concentration of rhodamine B dye. The decrease in catalytic activity with increase in concentration of dye is due to three reasons (Balcha et al 2016) (Saeed et al 2017) (Nisar et al 2021) (Adeel et al 2021):…”
Section: Effect Of Concentrationmentioning
confidence: 99%